Situations and mechanisms of non-contact knee injury in adult netball: A systematic review. (January 2021) - Mullally, Elaine M.; Atack, Alexandra C.; Glaister, Mark; Clark, Nicholas C.
Abstract: Objectives: Noncontact knee injuries in netball are a concern due to a range of negative consequences. To reduce the number of injuries, identifying the situation and mechanism of injury is important. This systematic review examined the literature reporting the situation and mechanism of noncontact knee injury in netball. Design: Systematic Review. Methods: PRISMA guidelines were followed and specific key-term combinations used to search databases. Descriptive and analytic-observational studies reporting the situation or mechanism of noncontact knee injury in females playing netball were included (evaluated using frequency counts). Results: Six articles were included (combined sample 11, 401). Players self-reported the situation of injury in five studies, only one study reported both the situation and mechanism of injury. Landing was the most reported situation of knee injury, representing 46.6% of all knee injuries whilst knee abduction (valgus) collapse was the most observed mechanism. Situation and mechanism of noncontact knee injury in netball were not adequately reported. Conclusions: Despite the variations in reporting methods, landing is the most common situation of injury. As only one study reported mechanism of injury, it is difficult to draw conclusions but the mechanism of noncontact knee injury in netball appears similar to those identified in other female athletes. Highlights: Knee injuries accounted for 15.1% of all injuries in netball. The most common situation of injury was landing occurring in 46.6% of knee injuries. Most landings (53.9%) were single-leg landings. Knee abduction (valgus) collapse was evident in 75% of knee injuries. In 68.8% of knee injuries, trunk position was an important consideration.